2020
DOI: 10.1186/s13048-020-00681-0
|View full text |Cite
|
Sign up to set email alerts
|

Rising serum CA-125 levels within the normal range is strongly associated recurrence risk and survival of ovarian cancer

Abstract: Background: In clinical practice alterations in CA-125 concentration within normal range in patients with ovarian cancer after first-line treatment are common. Even minor increase in CA-125 concentration is associated with patients' anxiety and difficult interpretation and counselling for clinicians. The aim of this study was to evaluate the significance of CA-125 fluctuations within reference level in patients who suffered from ovarian cancer with complete response after first-line treatment. Results: 168 pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
(17 reference statements)
0
20
0
Order By: Relevance
“…The study group was described in detail in a previous paper 27 . Briefly, 168 patients with epithelial ovarian cancer who achieved a complete response after first-line treatment were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The study group was described in detail in a previous paper 27 . Briefly, 168 patients with epithelial ovarian cancer who achieved a complete response after first-line treatment were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
“…As the current treatment measures are not promising, identifying reliable prognostic biomarkers is important to prolong the survival time of OC patients. In clinical practice, CA-125 and Human epididymis protein 4 ( HE4 ) were the most commonly used predictive markers (Piatek et al, 2020 ; Salminen et al, 2020 ). Besides, recent studies indicated that some microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) were also associated with the prognosis of OC (Nam et al, 2008 ; Qiu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The detailed characteristics of the study group was presented in our previous paper (10) and showed in Table 1. Almost 70% of women were diagnosed in advanced stage.…”
Section: Resultsmentioning
confidence: 99%
“…Patients' characteristics. The data in the table corresponds to those presented in the previous study(10).…”
mentioning
confidence: 78%
See 1 more Smart Citation